2018
DOI: 10.1111/jph.12780
|View full text |Cite
|
Sign up to set email alerts
|

The combined effect of 1‐methylcyclopropene and citral suppressed postharvest grey mould of tomato fruit by inhibiting the growth of Botrytis cinerea

Abstract: 1‐Methylcyclopropene (1‐MCP, 1 μl/L) and 1 × minimum fungicidal concentration (MFC) citral alone and in combination were used to treat on postharvest tomato fruits to investigate their influence on disease incidence and postharvest quality during fruit storage, which were stored at 90%–95% relative humidity and 25 ± 2°C. Weight loss, pH, hue angle (Hue°), total soluble solid (TSS), ascorbic acid content, firmness and antioxidant enzyme activities were evaluated after each storage period. 1 μl/L 1‐MCP or 1 × MF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 49 publications
0
3
0
2
Order By: Relevance
“…[69], Geotrichum citri-auranti [71], P. italicum [72], and Botrytis cinerea in Solanum lycopersicum [70]. Moreover, its efficacy has been evaluated in kiwi fruits [77], tomatoes [78], and citrus fruits [79] (see Table 2). In addition, reports indicate that combining citral with chitosan generates a synergistic effect, enhancing both mechanisms of action against various pathogens [70].…”
Section: Assay Concentration Effects Referencesmentioning
confidence: 99%
“…[69], Geotrichum citri-auranti [71], P. italicum [72], and Botrytis cinerea in Solanum lycopersicum [70]. Moreover, its efficacy has been evaluated in kiwi fruits [77], tomatoes [78], and citrus fruits [79] (see Table 2). In addition, reports indicate that combining citral with chitosan generates a synergistic effect, enhancing both mechanisms of action against various pathogens [70].…”
Section: Assay Concentration Effects Referencesmentioning
confidence: 99%
“…En una investigación más reciente, se utilizaron dosis de 220 g/L de tiabendazol para controlar el moho gris causado por B. cinerea. Los resultados mostraron que 12 días después de la inoculación, se observó en los frutos control un deterioro del 100%, mientras que en los frutos tratados con fungicida fue del 56.68% (Shenglong, Jihong, Shaoyang, Shuang & Li, 2019). Sin embargo, aun cuando se tienen resultados favorables en el control de los patógenos, su uso persistente e indiscriminado genera residuos tóxicos, nocivos para la salud a corto plazo (irritación de la piel y ojos, dolor de cabeza y náuseas) y a largo plazo (asma, diabetes y cáncer) (Ghazanfar et al, 2016;Kim, Kabir & Jahan, 2017).…”
Section: Fungicidas Sintéticos En Postcosechaunclassified
“…Los resultados evidenciaron una reducción de la infección ocasionada por B.cinerea en un 54 % (Rguez et al, 2018). También, cuando fue aplicado citral (1 µl/L) y se observó una reducción en la incidencia de la enfermedad del 37.4 % causada por B. cinerea, así como, un aumento de la actividad enzimática de la POD y PAL, relacionadas con la defensa de los frutos ante los patógenos (Shenglong et al, 2019). Además, los aceites esenciales como el caso del orégano cuando son incorporados en un recubrimiento a base de alginato de sodio y lecitina pueden reducir el crecimiento total de la carga microbiana, mohos y levaduras en la superficie de los frutos de jitomate Cherry (Pirozzi, Del Grosso, Ferrari & Donsì, 2020).…”
Section: Aceites Esencialesunclassified
“…For the preservation of fruits and vegetables, researchers usually combine two or more technologies to explore better preservation effects. 1‐methylcyclopropene (1‐MCP), as an ethylene action inhibitor, is an effective fresh‐keeping technology for fruit and vegetables, widely used in the apple industry around the world (Shenglong, Jihong, Shaoyang, Shuang, & Li, 2019). Many previous researchers have demonstrated that 1‐MCP treatment can not only visibly enhance some metabolic enzymes such as superoxide dismutase (SOD), catalase (CAT), and peroxidase (POD), but also reduced the harmful metabolites as lipoxygenase (LOX) and malondialdehyde (MDA), inhibited the softening and browning of fresh‐cut fruits (Kolniak‐Ostek, Wojdyło, Markowski, & Siucińska, 2014; Liu, Gao, Chen, Fang, & Wu, 2019; Saba & Watkins, 2019; Xu, Liu, Liu, et al, 2019; Xu, Liu, Xiao, & Fu, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…For the preservation of fruits and vegetables, researchers usually combine two or more technologies to explore better preservation effects. 1-methylcyclopropene (1-MCP), as an ethylene action inhibitor, is an effective fresh-keeping technology for fruit and vegetables, widely used in the apple industry around the world (Shenglong, Jihong, Shaoyang, Shuang, & Li, 2019).…”
Section: Introductionmentioning
confidence: 99%